2016
DOI: 10.1111/bcp.12925
|View full text |Cite
|
Sign up to set email alerts
|

The placebo response of injectable GLP‐1 receptor agonists vs. oral DPP‐4 inhibitors and SGLT‐2 inhibitors: a systematic review and meta‐analysis

Abstract: The response to placebo treatment was related to its active comparator, with injectable placebo GLP-1ra showing a relevant response on weight, whereas oral placebo DPP4i showed no significant response. These findings may suggest that subjective expectations influence T2DM treatment efficacy, which can possibly be employed therapeutically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 103 publications
(250 reference statements)
0
9
0
1
Order By: Relevance
“…Previous studies demonstrated that GLP-1 analogues were more potent in lowering HbA 1c levels than DPP-4 inhibitors [ 14 , 15 ]. However, there was no difference in the improvement of HbA 1c between lixisenatide and vildagliptin in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that GLP-1 analogues were more potent in lowering HbA 1c levels than DPP-4 inhibitors [ 14 , 15 ]. However, there was no difference in the improvement of HbA 1c between lixisenatide and vildagliptin in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adults show reductions in HbA 1c , glycaemic variability, body weight and insulin doses, increased time in the target glycaemic range, and improvements in cardiovascular risk factors and mortality compared with placebo [95,96]. The weight loss and glucose lowering with SGLT2 inhibitors appears less than that observed with GLP-1 receptor agonists [98], but this class of drugs appears very effective for treatment of DKD in adults [99,100]. SGLT2 inhibitors are approved in Europe and Japan for adults with type 1 diabetes.…”
Section: Treatmentmentioning
confidence: 99%
“…In Japan, DPP-4 inhibitors, including teneligliptin (TNL), are the most commonly prescribed antidiabetic drugs [12], and are suitable for both elderly and dialysis patients [13]. In addition, DPP-4 inhibitors are weight neutral [14][15][16]. It has been reported that, for patients responding inadequately to insulin, addition of a DPP-4 inhibitor to insulin therapy is more effective than a dose increase of insulin [10].…”
Section: Introductionmentioning
confidence: 99%